PENELITIAN MASALAH SOSIAL MIGRAN DI PERKOTAAN - Rukmini Dahlan (Politeknik Kesejahteraan Sosial, 2003)
Studies of Social Problems Faced by Migrants in Urban Area.Resident current migration from rural to urban region in various Province in Indonesiaevery years tend to increas. This social phenomenon brings implecation at appearance various social problem in urban region. Referring to taht, Social Welfare & Healt research and Development Institution, Department Of Social Affair execute research abaut Migran's Social Problem in Urban. The result of research indicated that all migran in general live in solid residen area and inhabit land which its ilegal status like a slum area. Generally they face various social problem, for example : Poorness, The Aged, Unemployed, Dirty environment and housing. To overcome the migran natural problem, the Govenment and also Community had given services but it have still diffrent charakteristic and incidental treatmen, so that the program not inwroughtly and unsutainable yet.Kata Kunci : Migran, Social problem, Urban area